2012
DOI: 10.1016/j.immuni.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Human Tissues Contain CD141hi Cross-Presenting Dendritic Cells with Functional Homology to Mouse CD103+ Nonlymphoid Dendritic Cells

Abstract: SummaryDendritic cell (DC)-mediated cross-presentation of exogenous antigens acquired in the periphery is critical for the initiation of CD8+ T cell responses. Several DC subsets are described in human tissues but migratory cross-presenting DCs have not been isolated, despite their potential importance in immunity to pathogens, vaccines, and tumors and tolerance to self. Here, we identified a CD141hi DC present in human interstitial dermis, liver, and lung that was distinct from the majority of CD1c+ and CD14+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
847
1
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 637 publications
(922 citation statements)
references
References 55 publications
43
847
1
11
Order By: Relevance
“…In light of these results, some investigators predicted that a CD11c hi CD1a + CD141 hi CLEC9A + TLR3 hi DC subtype should exist in nonlymphoid human tissues (28). In 2012, Haniffa et al (29) succeeded in identifying this population in human skin, skin-draining lymph nodes, liver, and lung. Through an extensive and detailed phenotypic identification of diverse DC subsets, the investigators demonstrated that human skin CD141 hi DCs are closely related to human blood CD141 + DCs and to mice crosspresenting cells (lymphoid CD8a + DCs and CD103 + migratory DCs) (29).…”
Section: Endritic Cells (Dcs) Belong To the Family Of Professionalmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of these results, some investigators predicted that a CD11c hi CD1a + CD141 hi CLEC9A + TLR3 hi DC subtype should exist in nonlymphoid human tissues (28). In 2012, Haniffa et al (29) succeeded in identifying this population in human skin, skin-draining lymph nodes, liver, and lung. Through an extensive and detailed phenotypic identification of diverse DC subsets, the investigators demonstrated that human skin CD141 hi DCs are closely related to human blood CD141 + DCs and to mice crosspresenting cells (lymphoid CD8a + DCs and CD103 + migratory DCs) (29).…”
Section: Endritic Cells (Dcs) Belong To the Family Of Professionalmentioning
confidence: 99%
“…In 2012, Haniffa et al (29) succeeded in identifying this population in human skin, skin-draining lymph nodes, liver, and lung. Through an extensive and detailed phenotypic identification of diverse DC subsets, the investigators demonstrated that human skin CD141 hi DCs are closely related to human blood CD141 + DCs and to mice crosspresenting cells (lymphoid CD8a + DCs and CD103 + migratory DCs) (29). Such a cross-presenting DC subtype in human epithelia was identified as one of the main targets for clinical studies aimed at inducing efficient CD8 + T cell responses against intracellular pathogens and tumors (30).…”
Section: Endritic Cells (Dcs) Belong To the Family Of Professionalmentioning
confidence: 99%
See 1 more Smart Citation
“…A specific subset of BDCA3 bright /CLEC9a + /Sirpa 2 DCs has recently been described in different human tissues (10)(11)(12)32). These DCs resemble murine CD8a + DCs in their ability to crosspresent exogenous Ags.…”
Section: Two Distinct Subsets Of Dcs Are Present In Human Afferent Lymentioning
confidence: 99%
“…In contrast, in the past few years, different subsets of DCs have been identified in human blood (BDCA1 + and BDCA3 + ) (7)(8)(9)(10) and skin (1,(11)(12)(13)(14)(15). In addition, we have lately gained access to a comprehensive depiction of DCs harbored in human lymph nodes (16)(17)(18), obtaining valuable information on migratory DC subtypes.…”
mentioning
confidence: 99%